Effects of the Teacher Discursive Moves on the Students' Reasoning Qualities in the context of Science Teaching: Discourse Analysis Approach - Yılmaz Soysal (Anı Publishing, 2019)
The basic purpose of the current study is to delve into the influences of the teacher discursive moves on the student-led cognitive contributions as in the form of reasoning quality by virtue of classroom discourse analysis approach. An experienced elementary science teacher and his 32, fifth grade students were the participants. In-class implementations were conducted through argument-based inquiry science teaching approach. The analysis of video-based data was carried out by means of systematic observations as a branch of sociocultural discourse analysis. Through data-based and theory-laden coding catalogues types of the enacted teacher-led discursive moves and student-led cognitive contributions as their reasoning qualities were coded analytically. Each teacher-led move and student-led cognitive contribution were counted, then, proportionally compared in order to determine the relations between discourse and cognition. Teacher-led moves were gathered under 10 higher categories. These were knowledge providing and evaluating moves, observing-comparing-predicting moves, communicating moves, monitoring moves, evaluating-critiquing-judging moves, challenging moves, seeking for evidencing moves, labelling-naming moves, inferencing moves and ensuring mutual respect moves. The knowledge providing and evaluating moves were negatively influencing on the student-led cognitive contributions, and since the observing-comparing-predicting moves were required less cognitive from the side of the learners, these moves were not functional in augmenting the cognitive contributions. Communicating and monitoring moves facilitated prior conditions for improving the student-led cognitive contributions. Evaluating-critiquing-judging and challenging moves held more concrete and visible effects in enhancing the cognitive contributions. Based on these, several recommendations were offered for the sake of the professional development of science teachers.